Pengaruh Media Audio Visual dalam Pembelajaran Rhytmic Activity Terhadap Motivasi Belajar Siswa Madrasah Aliyah Negeri - Fanny Nilna El-Fadillah; Citra Resita; Ega Trisna Rahayu (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to find out the truth about the effect of audio visual media in learning rhythmic activity on the motivation of students at Madrasah Aliyah Negeri which was carried out at MAN 1 Subang class XI Science. This research was carried out using a quantitative approach with experimental methods. The population in this study amounted to 134 students from four science classes. For the sample itself using cluster random sampling, for the sample taken in this study amounted to 57 students who were divided into four classes. The instrument used in this research is a questionnaire sheet that has been validated with a reliability coefficient. The reliability of the questionnaire is 0.712. This research uses SPSS22 media. There are three stages in this research, namely pretest, treatment, and posttest. The pretest was carried out to determine the initial motivation of students' learning before the treatment was carried out. After the pretest, the researcher then gave treatment, namely eight meetings. To analyze the data used, namely the calculation of the hypothesis that there is a significance value of 0.000 <0.05 so that there can be a relationship between pretest and posttest. Then the significance value (2 (tailed) is 0.037 which means that there is a significant effect from the results of the pretest and also the posttest. If tcount < ttable then Ho is accepted and if tcount > ttable then Ho is rejected. In this study tcount (-2.142) and ttable ( 1.672) it can be concluded that Ho is accepted.